2012
DOI: 10.1037/a0028702
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ecology on chimpanzee (Pan troglodytes) cultural behavior: A case study of five Ugandan chimpanzee communities.

Abstract: The influence of ecology on the development of behavioral traditions in animals is controversial, particularly for chimpanzees (Pan troglodytes), for which it is difficult to rule out environmental influences as a cause of widely observed community-specific behavioral differences. Here, we investigated 3 potential scenarios that could explain the natural variation in a key extractive tool behavior, "fluid-dip," among several communities of chimpanzees of the Pan troglodytes schweinfurthii subspecies in Uganda.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 68 publications
3
44
0
5
Order By: Relevance
“…In these foraging contexts, chimpanzees have overcome the constraints of their environment through technological innovations that served to increase their tool using opportunities and in some cases, tool modifications that enhance the profitability of tool-assisted foraging [62]. Although certain aspects of opportunity may trigger tool use, mere ecological opportunity may not be sufficient to support a tool using tradition [12,55]. Rather, emergence of a particular tool behaviour may require a certain threshold of abundance: (i) to provide repeated exposure to the target resource; (ii) to make the foraging for this food resource energetically profitable; (iii) to allow the tool user to gain sufficient experience with the tool using task; and/or (iv) to provide exposure to socially transmitted information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these foraging contexts, chimpanzees have overcome the constraints of their environment through technological innovations that served to increase their tool using opportunities and in some cases, tool modifications that enhance the profitability of tool-assisted foraging [62]. Although certain aspects of opportunity may trigger tool use, mere ecological opportunity may not be sufficient to support a tool using tradition [12,55]. Rather, emergence of a particular tool behaviour may require a certain threshold of abundance: (i) to provide repeated exposure to the target resource; (ii) to make the foraging for this food resource energetically profitable; (iii) to allow the tool user to gain sufficient experience with the tool using task; and/or (iv) to provide exposure to socially transmitted information.…”
Section: Discussionmentioning
confidence: 99%
“…Palaeoecological analysis has shown that the floristic composition of the Goualougo and neighbouring forests has varied considerably over the past 2580 years [10,11]. In their examination of the patterns of tool use among East African chimpanzee populations, Gruber et al [12] suggested that ancestral chimpanzee populations in the region may have been coping with harsher environments during the last Ice Age which prompted various behavioural innovations, such as extractive tool use.…”
Section: Introductionmentioning
confidence: 99%
“…12: 20160604 white-faced [14] and black [15] capuchins, and chimpanzees [4]. Foraging behaviour in non-human primates, particularly for generalist species, is influenced by ecological features and previous experience with problems in the environment, which may differ between populations [5,7,16]. Regarding probe use, the overall performance of our subjects in the task Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies on behavioural differences between ape populations suggest potential traditions as explanations for their distinct toolkits [3]. Wild chimpanzee populations differ in the techniques they employ to solve a foraging task and how they perceive objects as potential tools in accordance with their respective traditions, suggesting that cultural knowledge channels how apes approach new foraging problems [4,5]. Here, we examine how different traditions can affect the performance of wild bearded capuchin monkeys in tool-aided problem solving.…”
Section: Introductionmentioning
confidence: 99%
“…Às vezes, elas aparecem juntas e relacionadas; em outras, são tidas como fenômenos distintos ou diferenciados em termos de impacto e importância. À medida que as 'culturas de chimpanzés' foram identificadas como fenômenos "não genéticos", considerados parcialmente independentes (Laland, 2008b) ou complementares aos fatores ambientais (Gruber et al, 2012), mais pesquisadores têm enfocado seus mecanismos de transmissão e suas dinâmicas sociais.…”
Section: Cultura Em Versão Primatológicaunclassified